A finite element analysis on the biomechanical performance of implant-retained finger prostheses designed for Asians. Issue 11 (November 2022) - Shi, Jun; Sun, Yuxin; Han, Yan; Chai, Mi; Liu, Huxian; Wang, Juan
Summary: This study aims to explore the biomechanical performance of implant-retained finger prostheses of different lengths and diameters designed specifically for Asians under external loads from different directions by the finite element method. According to the metacarpophalangeal stumps (length: 4, 7, 10 mm, diameter: 3.5, 4.5 mm) retained in Asian patients with finger defects, six implant-retained finger prosthesis models of different lengths and diameters were designed in Solid Works 3D, transported to Abaqus, and constructed based on computerized tomography (CT). The finite element simulation of the finger prosthesis structure was performed using HyperMesh. The strain and stress distribution of the finger prosthesis models under three loads were calculated: axial force, lateral force, and lateral force with bending moments. As the load increased, the cancellous bone yielded first, while the dense bone and implant could withstand much higher loads than the cancellous bone. As the implant depth increased, the maximum strain of the cancellous bone increased significantly, but the effect of the implant diameter remained unclear. In addition, the structure could withstand large axial loads but was much less able to withstand both lateral forces and bending moments. The yielding and destruction of the implant-retained finger prostheses designed specifically for Asians are mainly attributed to cancellous bone. As the depth of the implants increases, the maximum strain of cancellous bone rises significantly. In addition, in the treatment of patients with finger defects, this method may be used to analyze and select which implant can withstand stronger stress according to the finger stumps of the patients with finger defects so that the most suitable implant and individual surgical plan for the patient can be designed.